Sawyer's duality principle for grand Lebesgue spaces. Issue 4 (10th December 2018) - Jain, Pankaj; Singh, Arun Pal; Singh, Monika; Stepanov, Vladimir D.
Abstract: The aim of this paper is to extend Sawyer's duality principle from the cone of decreasing functions of the Lebesgue space to the cone of decreasing functions of the grand Lebesgue space and to prove the boundedness of classical Hardy operators in the grand Lebesgue spaces.